Sustainability in Mexico a bibliometric analysis of the scientific research field in the last 28 years (2020)
The current economic, social, and environmental problems caused by global population growth and the over- exploitation of the planet's resources generate an increasing interest in sustainability driven studies as a priority issue for nations. The objective of the present paper is to apply bibliometric techniques for the analyses of the evolution of the scientific publications with focus on sustainability driven topics authored or coauthored by at least one researcher with affiliation to an institute located in the Mexican Republic. In total, 2,629 articles published in the last 28 years were identified by the designed methodical search in the Web of Science scientific database. The results are organized in tables that show the most influential articles in the area, the journals with the highest number of publications, the most productive authors, the most relevant research areas, and the most representative organizations. These results are complemented by visual network maps developed with the software VOSviewer. The results show the predominant thematic trends, in addition to a clear increase in participatory disciplines, with special emphasis on social disciplines. Keywords: Sustainability, Bibliometrics, Network Maps, Regional Analysis, Mexico. JEL Classification: Q56, Q01, Y1. Received: 21/07/2020. Accepted: 05/11/2020.  Published: 01/12/2020